Acquirers and financial constraints: Theory and evidence from emerging markets. (October 2021) - Mukherjee, Rahul; Proebsting, Christian
Highlights: Model of acquisitions where domestic acquirers are subject to borrowing constraints. Predicts fire-sales and novel counteracting selection effect for domestic acquirers. Regression evidence on stakes and divestitures supports theoretical predictions. Selection effect contributes to 12% rise in stakes and 30% fall in divestiture rate. Abstract: Financial crises in emerging market economies induce diverging patterns of ownership stakes and subsequent divestiture rates among domestic and foreign acquirers. We rationalize these empirical findings in a tractable model where domestic acquirers are subject to borrowing constraints. In contrast to standard fire-sale effects operating for acquisitions by foreign acquirers, acquisition patterns of domestic firms are shaped by a novel counteracting selection effect, resulting in larger acquired stakes and more persistent ownership. We present empirical evidence consistent with the model's predictions using a large dataset of domestic and cross-border emerging market acquisitions over 1990–2007. The estimated contribution of selection effects is quantitatively significant, leading to 12% increases in stakes, 25% increases in full acquisitions, and 30% declines in divestiture rates among crisis-time domestic acquisitions. Our results demonstrate how financial crises can have both short- and long-run effects through the market for corporate control, by changing the set of acquirers and how long acquirers keep ownership.